Morbidity Characteristics in Toddlers in the Coastal Area of Bengkulu City - Kurniati, Neng; Yulyani, Linda; Ramadhaniati, Fitri (JURNAL KEBIDANAN, 2023)
The morbidity of a region is an important indicator in the assessment and planning of health programs. Children under the age of five are a group that is susceptible to disease. This study aims to look at the characteristics of the incidence of morbidity in toddlers in the coastal area of Bengkulu City. This research is quantitative research with a rapid survey approach. The research was conducted in 30 households in the coastal area of Bengkulu city. The research sample was taken using the cluster technique and simple random sampling. The research was conducted in 30 sub-districts and there were 210 samples in this study. The data collected were analyzed using univariate analysis to see the frequency distribution of morbidity in toddlers in the Bengkulu City Coastal Area. The results showed that of the 210 respondents in this study, 93.3% had experienced pain in the last 12 months. The types of disease experienced by the majority of respondents were Acute Respiratory Infection (ARI) (42.2%), and diarrhea (33.8%), besides there were diseases such as pneumonia (1.9%), pulmonary TB (1%), measles (12.4%) and worms (8.6%). The majority of respondents in the study accessed healthcare facilities when they were sick (89.5%). For measurements of weight, height, and Mid Upper Arm Circumference (MUAC), the majority of respondents in this study obtained them at the Integrated Healthcare Center (Posyandu) and Public Health Center (Puskesmas).